PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP FINANCIAL DISTRESS DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN PERDAGANGAN ECERAN YANG TERDAFTAR DIBURSA EFEK INDONESIA PERIODE 2016-2020 - Meita Sekar Sari; Arie Sarjono Idris; Dewi Silvia; Suhendar Suhendar; Nur Salma; Ines Aryani (ITB AAS Indonesia Surakarta, 2022)
This study aims to determine the results of the effect of profitability and liquidity on financial distress with capital structure as a moderating variable in retail trading companies listed on the Indonesia Stock Exchange for the 2016- 2020 period. The sample used in this study amounted to 11 retail trading companies listed on the IDX. This study uses quantitative informasi and the type of informasi used in this study is secondary informasi in the form of company financial statements obtained from the official web of the Indonesia Stock Exchange. Based on the results of statistical tests using the SPSS 25 program, it can be concluded that: 1) Profitability proxied to ROA has a positive and significant effect on financial distress in retail trading companies listed on the Indonesia Stock Exchange for the 2016- 2020 period. 2) Liquidity as proxied by the Current Ratio has a negative and significant effect on financial distress in retail trading companies listed on the Indonesia Stock Exchange for the 2016- 2020 period. 3) ROA and Current Ratio simultaneously have a significant and significant effect on financial distress. 4) Capital structure moderates the effect of ROA on financial distress by weakening indications of bankruptcy. 5) Capital structure moderates the effect of the Current Ratio on Financial distress by weakening the indication of bankruptcy.